CARA MENSOSIALISASIKAN NILAI-NILAI KEPADA ANAK OLEH ORANGTUA DALAM KELUARGA PENAMBANG EMAS (STUDI: JORONG SARIAK TABA NAGARI LUBUK GADANG KECAMATAN SANGIR KABUPATEN SOLOK SELATAN) - Depnawati, Depnawati; Erianjoni, Erianjoni; Oktavia, Dian Anggraini (Pendidikan Sosiologi, 2014)
This research is motivated by socialization which is run by his parents in fact running properly. During the father worked in the mining socialize mother who values her children as teach their children the Koran, read the Quran, teaches reading prayers, invite children to pray. Although the father was busy working in the mine, but the father also plays a role in disseminating the values to their children. Therefore, this study aimed to determine how to disseminate the values to children by their parents in the family miners.The approach used is descriptive qualitative approach. Determination of purposive informant done. Data was collected through observation, interviews, and documentation. The unit of analysis is the family miners. Data analysis method used is descriptive analysis of the data was analyzed according to the interactive model (Interactive Model Of Analysis) Miles & Hubermas.The results showed in general how to disseminate the values to children by their parents in the family miners in Jorong Sariak Taba is seen that parents who work as gold miners disseminate good values to their children and teach their children by bringing material values, parents also teach vital values and spiritual values.